2015
DOI: 10.3892/mmr.2015.3799
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein-γ promotes migration of MCF7 breast cancer cells by activating extracellular-signal regulated kinase pathway and breaking cell-cell junctions

Abstract: Synuclein-γ (SNCG), a synuclein family member, promotes migration, invasion and metastasis of tumor cells; however, the mechanism remains unclear. The present study investigated the effect of SNCG on malignant phenotypes of MCF7 cells using cell proliferation analysis, cell migration assays and wound healing assays, and verified its effects on extracellular‑signal regulated kinase (Erk) activation and epithelial to mesenchymal transition‑related markers using western blotting. The results indicated that SNCG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In migration assays, SNCG silencing significantly decreased cell migration in cell lines from both ECC and ICC. This finding was consistent with previous reports in breast cancer, hepatocellular carcinoma, and gallbladder carcinoma 38–40 . The results of in vitro assays suggested that the role of SNCG may be associated with cell migration, which is generally linked to cell differentiation and metastasis regardless of the origin of the biliary tract tumor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In migration assays, SNCG silencing significantly decreased cell migration in cell lines from both ECC and ICC. This finding was consistent with previous reports in breast cancer, hepatocellular carcinoma, and gallbladder carcinoma 38–40 . The results of in vitro assays suggested that the role of SNCG may be associated with cell migration, which is generally linked to cell differentiation and metastasis regardless of the origin of the biliary tract tumor.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that SNCG increases cell proliferation in gallbladder, colorectal, and prostate cancer 30,38,41 . However, other studies on breast cancer and pancreatic cancer showed no significant correlation between SNCG expression and cell proliferation 9,39 . These inconsistencies may result from differences in the functions of SNCG expression in each cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is expressed at presynaptic terminals in the brain and the peripheral nervous system (35). It promotes migration, invasion and metastasis of tumor cells (36), which have proven that expression of SNCG protein is elevated in the advanced stages of various types of cancers, including ovarian (37), lung, liver (38), esophagus (39), colon (38) and in particular, breast (40,41). For example, Singh and Jia (41) revealed that SNCG protein expression was correlated with pathological factors, including lymph node metastasis, tumor size and stage, and follow-up revealed that the survival rate of patients with SNCG -positive protein expression were significantly lower than the patients with negative expression for 438 cases with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-invasive capacity of α-synuclein provides a biological explanation for its upregulation in atypical and anaplastic meningiomas. Although there is few evidence for α-synuclein-mediated cell invasiveness, γ-synuclein has been shown to promote cell migration and invasion in different types of tumor cells such as oral squamous cell carcinoma [12], breast cancer [21], and gastric cancer [22]. …”
Section: Discussionmentioning
confidence: 99%